2013
DOI: 10.1016/j.molcel.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Paradoxical Components in Biological Circuits

Abstract: A recurring theme in biological circuits is the existence of components that are antagonistically bifunctional, in the sense that they simultaneously have two opposing effects on the same target or biological process. Examples include bifunctional enzymes that carry out two opposing reactions such as phosphorylating and dephosphorylating the same target, regulators that activate and also repress a gene in circuits called incoherent feedforward loops, and cytokines that signal immune cells to both proliferate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
151
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(166 citation statements)
references
References 102 publications
7
151
0
3
Order By: Relevance
“…Similar biphasic filters have been found in numerous other systems (Hart and Alon, 2013;Kato et al, 2014;Nagel and Doupe, 2006); there they are proposed to support efficient coding (Atick and Redlich, 1990;Zhao and Zhaoping, 2011). Here, we add another aspect that makes biphasic filters advantageous: the two lobes correspond to two neuronal response features -tonic and phasic -and signal distinct song features -song amount and bout number.…”
Section: Linking Computations In the Auditory Pathway With Female Behmentioning
confidence: 54%
“…Similar biphasic filters have been found in numerous other systems (Hart and Alon, 2013;Kato et al, 2014;Nagel and Doupe, 2006); there they are proposed to support efficient coding (Atick and Redlich, 1990;Zhao and Zhaoping, 2011). Here, we add another aspect that makes biphasic filters advantageous: the two lobes correspond to two neuronal response features -tonic and phasic -and signal distinct song features -song amount and bout number.…”
Section: Linking Computations In the Auditory Pathway With Female Behmentioning
confidence: 54%
“…Rather, they operate in a large number of biological contexts, spatial, and temporal scales and functional states exemplified by protein‐specific properties such as reaction mechanisms, substrate/ motif binding and complex formation. In addition, properties of protein networks such as information processing, noise, adaptability, robustness, and even seemingly paradoxical arrangement of components and functions, such as enzyme promiscuity 19, 20, 21, 22, 23, 24, 25, 26. Moreover, a protein can exist with different variant sequences due to splicing or mutations, and be subject to different PTMs at different sites, resulting in a vast number of theoretical combination of PTMs, known as “mod‐forms”, see for example the histone‐code 18.…”
Section: Introductionmentioning
confidence: 99%
“…A biexponential function can be used to fit these curves, wherein one exponent corresponds to the timescale of activation and one corresponds to the timescale of inhibition. Hart and coworkers (12,13) identified that network motifs with bifunctional enzymes, which control activation and inhibition, can be thought of as paradoxical, because the same stimulus seems to control the activation and the inhibition in response to the same stimulus. This circuit is a special case of the incoherent feedforward loop (13).…”
mentioning
confidence: 99%
“…Hart and coworkers (12,13) identified that network motifs with bifunctional enzymes, which control activation and inhibition, can be thought of as paradoxical, because the same stimulus seems to control the activation and the inhibition in response to the same stimulus. This circuit is a special case of the incoherent feedforward loop (13). Paradoxical signaling has been identified in different contexts; examples include cellular homeostasis, cell population control, and actin dynamics through Arp2/3 and Arpin (12)(13)(14)(15).…”
mentioning
confidence: 99%